Jamaica : Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2001)
The statistical data on gross domestic product savings and investment, gross fixed capital formation, output of selected commodities, selected information on the bauxite/alumina sector, public sector balance, financing operations of the general government, and central government revenue and grants of Jamaica are presented in the paper. The data on summary accounts of the banking system, distribution of commercial banks' loans and advances, balance-of-payments summary, external public debt outstanding, exchange rates and related economic indices are also presented.